2003
DOI: 10.1023/a:1026107405399
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Ketogenic diets have been used in the treatment of refractory childhood epilepsy for almost 80 years; however, we know little about the underlying biochemical basis of their action. In this study, we evaluate oxidative stress in different brain regions from Wistar rats fed a ketogenic diet. Cerebral cortex appears to have not been affected by this diet, and cerebellum presented a decrease in antioxidant capacity measured by a luminol oxidation assay without changes in antioxidant enzyme activities--glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(51 citation statements)
references
References 28 publications
3
43
0
1
Order By: Relevance
“…Conversely, in a hypoglycemic in vivo model, ( d or l )-βOHB, but not AcAc prevented hippocampal lipid peroxidation (Haces et al, 2008; Maalouf et al, 2007; Marosi et al, 2016; Murphy, 2009; Tieu et al, 2003). In vivo studies of mice fed a ketogenic diet (87% kcal fat and 13% protein) exhibited neuroanatomical variation of antioxidant capacity (Ziegler et al, 2003), where the most profound changes were observed in hippocampus, with increase glutathione peroxidase and total antioxidant capacities.…”
Section: Ketone Bodies Oxidative Stress and Neuroprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in a hypoglycemic in vivo model, ( d or l )-βOHB, but not AcAc prevented hippocampal lipid peroxidation (Haces et al, 2008; Maalouf et al, 2007; Marosi et al, 2016; Murphy, 2009; Tieu et al, 2003). In vivo studies of mice fed a ketogenic diet (87% kcal fat and 13% protein) exhibited neuroanatomical variation of antioxidant capacity (Ziegler et al, 2003), where the most profound changes were observed in hippocampus, with increase glutathione peroxidase and total antioxidant capacities.…”
Section: Ketone Bodies Oxidative Stress and Neuroprotectionmentioning
confidence: 99%
“…Taken together, most reports link βOHB to attenuation of oxidative stress, as its administration inhibits ROS/superoxide production, prevents lipid peroxidation and protein oxidation, increases antioxidant protein levels, and improves mitochondrial respiration and ATP production (Abdelmegeed et al, 2004; Haces et al, 2008; Jain et al, 1998; Jain et al, 2002; Kanikarla-Marie and Jain, 2015; Maalouf et al, 2007; Maalouf and Rho, 2008; Marosi et al, 2016; Tieu et al, 2003; Yin et al, 2016; Ziegler et al, 2003). While AcAc has been more directly correlated than βOHB with the induction of oxidative stress, these effects are not always easily dissected from prospective pro-inflammatory responses (Jain et al, 2002; Kanikarla-Marie and Jain, 2015; Kanikarla-Marie and Jain, 2016).…”
Section: Ketone Bodies Oxidative Stress and Neuroprotectionmentioning
confidence: 99%
“…A role for mitochondrial bioenergetics has also been suggested to underlie the protective effects of the KD. For example, the KD has been shown to produce mitochondrial biogenesis (Bough et al, 2006), a decrease in mitochondrial ROS (Maalouf et al, 2007) due to upregulation of the uncoupling protein UCP2 (Sullivan et al, 2004), increase the cellular antioxidant capacity (Ziegler et al, 2003; Costello and Delanty, 2004; Nazarewicz et al, 2007), and in vitro studies have demonstrated that ketosis byproducts have the ability to prevent mtDNA deletions and cell death (Yamamoto and Mohanan, 2003; Santra et al, 2004). The KD has recently been demonstrated to improve the mitochondrial redox status in rats fed the diet for 3 weeks, which may improve the ability of the brain to resist metabolic changes and oxidative stress which partly underlies the occurrence of seizures (Jarrett et al, 2008b).…”
Section: 1 Targeting Mitochondrial Oxidative Stress In Epilepsy Thementioning
confidence: 99%
“…Ketones can oxidize coenzyme Q, thus decreasing mitochondrial free radical formation. Additionally, the reduction of NAD favors reduction of glutathione, which ultimately favors destruction of hydrogen peroxide by glutathione peroxidase reaction [46,47]. …”
Section: Ketones Metabolism and The Brainmentioning
confidence: 99%